Food quality assurance of crude palm oil: a review on toxic ester feedstock - Ainul Farhani, Ahmad Nizam; Mohd Sabri, Mahmud (EDP Sciences, 2021)
Palm oil, the commodity produced mainly in Indonesia and Malaysia, is widely used for deepfrying of fast food and food derivatives. European and American markets of palm oil are affected by the concern of the toxicity potential from monochloropropanediol esters (MCPDE) and glycidyl ester (GE) that are undesirably produced from monoacylglycerol (MAG), diacylglycerol (DAG) and chlorine in refineries. Improvement of oil palm plantation, fruit harvest and oil extraction process in palm oil mills is necessary before the refinery process so that hydrolysis reactions that produce MAG and DAG and chlorine contamination can be minimized in crude palm oil (CPO). This review focuses on the quality control currently employed in the mills especially in managing free fatty acid (FFA) formation as the indicator of the hydrolysis reactions along with other quality control parameters and the reduction of chlorine content.